Development of fluorescent and colorimetric rhodamine chemosensors for selected metal ions / Cheah Poh Wei - Cheah , Poh Wei (2021)
Metal pollution as a result of industrialisation has been a recurring environmental issue for humans and aquatic ecosystem. However, conventional methods used to detect these metals are deemed inconvenient and impractical for on-site sensing, hence an alternative method is highly sought after. Thus far, rhodamine based probes have shown encouraging results in this area but limitations such as low sensitivity and interference from other metal ions still persist. Therefore, in an effort to improve the efficacy of metal detection, four rhodamine Schiff base chemosensors were synthesized from the condensation of rhodamine B hydrazide with different ketone and aldehydes, namely 2,4,6-trihydroxybenzaldehyde, 3-hydroxy-4-methoxybenzaldehyde, 6-bromoveratraldehyde, and methyl ethyl ketone to form sensors THB, HMB, BVT, and MEK respectively. Characterization of the chemosensors were carried out with FTIR, 1H-NMR, 13C-NMR, and X-ray crystallography. The selectivity, sensitivity, and specificity of each sensor towards various metal ions were studied with UV-vis and fluorescence spectroscopy. Results obtained have revealed different metal preferences of each sensor through colour changes, enhanced absorbance, and fluorescence, whereby BVT, HMB, and MEK were selective towards Al3+ and Sn2+ ions, while THB was shown to be selective towards Cu2+ ions. The detection limits of these sensors were also evaluated and compared with WHO acceptable limit of Al3+, Cu2+, and Sn2+ in drinking water. Among the sensors synthesized, THB displayed the lowest limit of detection for Cu2+ (0.48 M) followed by MEK, HMB, and lastly BVT towards their respective target metal ion. Additionally, the formation of the sensor-metal complex was confirmed to be reversible through the utilization of EDTA, with MEK having the highest reproducibility (up to 6 cycles) amongst the four. While the binding stoichiometry determined through Job’s plot was different for each sensor, the most probable binding site involves the amide carbonyl of rhodamine spirolactam ring, as revealed by the shifting of this characteristic peak to a lower frequency in the sensor-metal complex FTIR spectra. Then, the concept of these four Schiff base ligands as an on-site sensor that provides ‘naked-eye’ recognition of Al3+, Cu2+, and Sn2+ in 100% aqueous condition was also effectively developed with paper test strips. Furthermore, the potential of these Schiff base ligands as cancer inhibitory agents were studied using colorectal adenocarcinoma cell line (HT-29) and non-cancerous colon cell line (CCD-18Co) via MTT assay. Both BVT and HMB were not cytotoxic towards cancerous HT-29 cells, but MEK exhibited comparable cytotoxicity with cisplatin and THB was weakly cytotoxic. Nonetheless, we have successfully synthesized four new rhodamine Schiff base ligands that provides rapid “naked-eye” detection through off-on colour changes in this study. The convenience, portability, and facile synthesis of these ligands further suggest its potential application as an on-site testing kit for the detection of Al3+, Cu2+ and Sn2+.